2016
DOI: 10.1590/0001-3765201620140590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage system on yield and weed populations of soybean ( Glycin Max L.)

Abstract: Field experiment was conducted at Agricultural and Natural Resources Research Center of Golestan Province, Iran, to determine the effects of tillage system and weed management regime on yield and weed populations in soybean (Glycin max L.). The experimental design was a split plot where the whole plot portion was a randomized complete block with three replicates. Main plots were tillage system: 1-Notill row crop seeding, 2-No-till seed drilling, 3-Tillage with disc harrow and drill planting, 4-Tillage with chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…These results are similar to those obtained by Seadh and Abido (2013), Akter et al (2016) and Hosseini et al (2016). c-Seed, straw and biological yield.…”
Section: -Effect Of Plant Spacing and Weed Control Treatments On Weedssupporting
confidence: 90%
“…These results are similar to those obtained by Seadh and Abido (2013), Akter et al (2016) and Hosseini et al (2016). c-Seed, straw and biological yield.…”
Section: -Effect Of Plant Spacing and Weed Control Treatments On Weedssupporting
confidence: 90%
“…In Malawi, conservation tillage practices increased SWS up to 37.5%, maize grain yield by 10.6%, and WUE by 11.1% compared with CT (TerAvest et al, 2015). Hosseini et al (2016) also reported a 16.0-24.6% increase in soybean grain yield under NT than CT.…”
Section: Introductionmentioning
confidence: 89%
“…Conservation tillage practices, namely; reduced tillage (RT), notillage (NT), stubble-mulching (SM), subsoiling (SS), and tied-ridge, provide instant benefits to farmers such as increasing rainwater harvesting, improved soil water storage (SWS) (Kargas et al, 2012;TerAvest et al, 2015), WUE (Miriti et al, 2012), and crop yields (Blanco-Canqui et al, 2017;Hosseini et al, 2016). In Kenya, a 4-year study by Miriti et al (2012) reported up to 9.1 and 31.7% increase in cowpeas grain yield and WUE, respectively under tied-ridge when compared with conventional tillage (CT).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean (Glycine max (L.) Merril.)) is the most important and most convenient source of vegetable protein and vegetable oil known to mankind, with an importance in eradicating malnutrition, especially in developing countries (Agam et al, 2019;Idrisa et al, 2010;Pratap et al, 2011).…”
Section: Introductionmentioning
confidence: 99%